2012
DOI: 10.2298/vsp111007020o
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve endocarditis during brucellosis relapse

Abstract: A combined antibiotic therapy and surgery reduce complications and mortality associated with Brucella endocarditis and improve quality of patients' life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The patient improved by mitral valve replacement accompanied with a 6-month postoperative medical therapy. Prior to this report, no cardiovascular involvement during the relapse episode had been described in a study reported the largest series of patients with brucellosis (21). Infection of tricuspid valve in brucella endocarditis is extremely rare.…”
Section: Discussionmentioning
confidence: 80%
“…The patient improved by mitral valve replacement accompanied with a 6-month postoperative medical therapy. Prior to this report, no cardiovascular involvement during the relapse episode had been described in a study reported the largest series of patients with brucellosis (21). Infection of tricuspid valve in brucella endocarditis is extremely rare.…”
Section: Discussionmentioning
confidence: 80%